MOLYBDENUM(VI) SPECIATION IN SULFIDIC WATERS: - STABILITY AND LABILITY OF THIOMOLYBDATES - Erickson B.E.; Helz G.R. (My University, 2000)
Molybdenum in sedimentary rocks and sediments has evoked interest as a paleo-environmental indicator of reducing conditions. This application demands better understanding of Mo deposition mechanisms and in turn, requires improved knowledge of Mo speciation in anaerobic natural waters. In sulfidic solution, molybdate undergoes sulfidation in four steps that conserve MoVI and lead to tetrathiomolybdate: MoOxS4-x2- + H2S(aq) # MoOx-1S5-x2- + H2O(l), 1 =< x =< 4. Equilibrium constants (K(4-x)(5-x)) and rate constants (k(4-x)(5-x)) have been measured by UV-visible spectroscopy. At 25°C, I = 0.8-2.2 M, log K01 = 5.19 +/- 0.03, log K12 = 4.80 +/- 0.12, log K23 = 5.00 +/- 0.13, log K34 = 4.88 +/- 0.28. The monothio to trithio-intermediates have negligible stability fields. If H2S(aq) increases slowly enough to maintain near-equilibrium conditions, a sharp switch will occur from MoO42- to MoS42- at ~11 μM H2S(aq) (298 K, 1 atm). Sulfide actuation of the switch depends on aH2S4, so a ~3-fold change in aH2S produces a ~100-fold change in MoO42-/MoS42-. Conversion of the predominant anion from a hard to a soft base alters Mo's geochemical behavior, increasing its susceptibility to scavenging. Because each successive sulfidation reaction is ~1 order of magnitude slower than the previous one, dithio- # trithio- and trithio- # tetrathiomolybdate equilibria might not be achieved in seasonally or intermittently sulfidic waters. In such environments, unstable mixtures of intermediate thiomolybdates can predominate, contradicting thermodynamic predictions. The sulfidation reactions are acid catalyzed. Anoxic sediment porewaters, which are enriched relative to overlying waters in Bronsted acids, will promote conversion of molybdate to thiomolybdates. This may account for observations that Mo deposition in euxinic environments occurs often by diagenetic pathways rather than by water column scavenging. Slow hydrolysis and oxidation of MoS42- suggests that it could serve as a reservoir of fixed, but acid-labile sulfide in oxic waters.